2004
DOI: 10.1097/01.brs.0000107235.47465.08
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Pain, Disability, and Quality of Life in Patients With Common Low Back Pain

Abstract: Clinically relevant improvements in pain may lead to almost unnoticeable changes in disability and quality of life. Therefore, these variables should be assessed separately when evaluating the effect of any form of treatment for low back pain. The influence of pain and disability on quality of life progresses while they last, and doubles in 14 days. In acute and subacute patients, this increase is not dependent on the previous duration of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
132
3
27

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(172 citation statements)
references
References 25 publications
10
132
3
27
Order By: Relevance
“…Although a preliminary study with a small sample, the results show that the clinical outcomes of pain and disability have excellent correlation (r=0.82; p<0.01) and is in accordance with expectations from the clinical point of view and with the literature 25 . Similarly, the STarT Back questionnaire of our sample for low and medium risk for poor prognosis correlated moderately with pain and disability (r=0.68 and r=00:57, respectively).…”
Section: Discussionsupporting
confidence: 72%
“…Although a preliminary study with a small sample, the results show that the clinical outcomes of pain and disability have excellent correlation (r=0.82; p<0.01) and is in accordance with expectations from the clinical point of view and with the literature 25 . Similarly, the STarT Back questionnaire of our sample for low and medium risk for poor prognosis correlated moderately with pain and disability (r=0.68 and r=00:57, respectively).…”
Section: Discussionsupporting
confidence: 72%
“…Utilities were estimated from mean pain VAS scores for the two treatment arms, using a relationship between pain VAS and EQ-5D utility sourced from a study of back pain. 137 The latter gave a much steeper gradient in utility loss with increasing pain than that derived from a study of varicose veins (a utility decrement of 0.035 per 1% increase in pain VAS compared with 0.0026; 86 see Utility values), suggesting that the QALY benefit of RFA compared with surgery reported by Adi et al 135 may be overestimated by over 10 times. Costs were taken from the Finnish trial.…”
Section: Assessment Of Cost-effectivenessmentioning
confidence: 69%
“…The suggestion that the number of fractures is also an important determinant of the worsening of quality of life has been supported by the observation that the impact of any recent vertebral fracture is more marked in the patients who had already sustained a previous vertebral deformity [5]. Moreover, it is important to note that in elderly women, back pain is multifactorial and is often the result of osteoarthritis, a protruded disk, and muscle diseases [18,33]. In our study population, we found that reduced values of stiffness are associated to a lowering of health-related quality of life; however, the association was no longer significant after adjusting for potential confounders such as age, comorbidities, and fractures.…”
Section: Discussionmentioning
confidence: 99%